Efeito fotoelétrico no ensino médio por meio de experimentos - Silva, Gildo Sandro da (2020)
The photoelectric effect, as well as other themes focused on modern physics, are generally less explored and demonstrated experimentally in the classroom in a significant way, because the curriculum of classical physics teaching is extensive in the 3rd grade of high school. Thus, the time required to apply the material in question is insufficient, in addition, the cost of acquiring the devices for a modern physics laboratory is often very expensive. The objective of this work was to plan and carry out a Modern Physics class, proposing a teaching-learning methodology in a meaningful way, with the application of simple experiments to study the photoelectric effect in the classroom. Thus, low-cost materials with easy access to high school teachers and students were used. Therefore, the experiments demonstrated how the phenomenon occurs, one of them, allowed the perception of the effect, through the incidence of light, with different colors in the LDR sensor and its relationship with the electric current produced in the circuit. The other experiment explored how electrical current occurs in the circuit, based on the photoelectric effect produced by the incidence of light on a photovoltaic plate. A light emitting circuit was also structured for the experimental interaction between the two circuits already mentioned. In this work, the Theory of David Paul Ausubel and Marco Antonio Moreira was used, emphasizing meaningful learning. The methodology was applied to a 3rd year class at a school in Várzea Grande-MT. The contents were worked through the educational product, with its teaching-learning sequence with reduced classes in the investigative perspective. Its application was subjected to a quantitative assessment by comparing the results between, the pre-test and the post-test. Therefore, it was observed that students improved their performance significantly and efficiently from the topic photoelectric effect, where it is conceived of the analytical results achieved in this work.